Histórias e superstições: narrativas e experiências de transformações da cultura popular de Catalão (GO) - Soares, Vivian Cristiany Oliveira (2006)
This work aims at considering superstitions both in the context social, cultural changes and as an essential part of human being, since it makes part of culture. We search to discuss the transformations of superstition in the modern society based on the oral accounts of people who moved from countryside to the city of Catalão, State of Goiás. We has tried to identify how these people consider superstitions now and understand their rural past, marked by oral tradition and popular beliefs, and so to know how popular culture rereads superstitions in the present. In these individual s speech, we have noted some conceptions of past countryside/hindrance and present city/progress which led us to rethink of theses spaces as different and complimentary.